Differences Across Illness Perceptions in Inflammatory Bowel Disease and Their Relationships to Psychological Distress and Quality of Life. (July 2017) - Tribbick, Davina; Salzberg, Michael; Connell, William; Macrae, Finlay; Kamm, Michael; Bates, Glen; Cunningham, Georgina; Austin, David; Knowles, Simon
Abstract : Patients with greater inflammatory bowel disease activity readily identify poorer psychosocial outcomes; however, the role of gender, disease type, and individual illness perceptions facets are less well known. This study aimed to characterize the role of illness perceptions, gender, and disease type on anxiety, depression, and quality of life. Eighty-one patients diagnosed with inflammatory bowel disease (39 men, mean age 35 years) attending a tertiary hospital outpatient clinic were studied. Questionnaires used included the Manitoba Index, the Brief Illness Perceptions Questionnaire, Hospital Anxiety and Depression Scale, and the World Health Organization Brief Quality of Life Scale. Female patients with active disease tended to report increased anxiety, depression, and reduced quality of life. Regarding illness perceptions, patients with Crohn disease reported significantly more concerns about its chronicity, while female patients reported being significantly more concerned about the impact of their illness on identity, chronicity, overall concern, and having a greater emotional impact. Hierarchical regression indicated that 36% of depression, 42% of anxiety, and 57% of quality of life could be accounted for by disease activity and type, gender, and illness perceptions. The findings suggest that in addition to a patient's perceived disease status, gastroenterology nurses should also be aware that patient gender and their perceptions of illness play a significant impact not only on anxiety and depression but also on quality of life. Increased disease activity is associated with more severe anxiety and depression and reduced quality of life. Female patients are also at a greater risk of reporting negative illness perceptions and increased levels of anxiety, depression, and lower quality of life.